SEXUALITY IN CONTEMPORARY KAZAKH ART AND LITERATURE: REPRESENTATIONS AND SOCIOCULTURAL IMPLICATIONS - YERBOSSYN Aruzhan (Theoretical Hypotheses and Empirical Results, 2025)
This article explores the evolving representations of sexuality in contemporary Kazakh art, literature, and popular music. It traces the shift from traditional norms—where intimacy was veiled through poetic suggestion—to a postmodern aesthetic that embraces openness, irony, and symbolic layering. Through analyses of recent literary works, aitys performances, and music lyrics by artists such as Israil Saparbay, Alisher Rakhath, RaiM, and Kalifarniya, the article demonstrates how Kazakh creators use sexuality not merely for provocation but as a tool for cultural reflection. These representations challenge conservative expectations, foreground bodily expression, and negotiate identity in a society shaped by both national heritage and global influence. The study argues that sexuality in Kazakh contemporary culture functions as a dynamic site of artistic innovation and sociopolitical dialogue